Aeolian Dust Provenance in Central East Antarctica During the Holocene: Environmental Constraints From Single‐Grain Raman Spectroscopy. Issue 16 (29th August 2019) - Paleari, Chiara Ileana; Delmonte, Barbara; Andò, Sergio; Garzanti, Eduardo; Petit, Jean Robert; Maggi, Valter
Abstract: We analyzed the single‐grain mineralogical composition of aeolian dust transported to central East Antarctica for provenance purposes. Comparison with data from the last glacial period shows for the first time disappearance of carbonates during the Holocene related to sea level rise and suppressed deflation from the Argentinean continental shelf, exposed during Marine Isotope Stage 2. Zeolites, related to alteration of volcanic glass in the subglacial/periglacial environment of Patagonia, show a similar behavior. The remaining minerals, remarkably similar between the two climatic periods, are compatible with a Pampean and Patagonian provenance, but Holocene data show a more pronounced volcanic and metamorphic imprint and presence of minerals related to warm climate weathering environments compatible with an additional contribution from subtropical latitudes of South America. These results do not imply a major large‐scale reorganization of atmospheric circulation after the last climatic transition. Plain Language Summary: Aeolian mineral dust particles transported through the atmosphere from the austral continents to the Antarctic ice sheet represent a tracer of atmospheric circulation and transport, as well as being a source of information about environmental conditions within dust source regions. Many lines of evidence suggest that central East Antarctic dust is sourced from South America during the last glacial period, whereas there is not a general consensus about dust provenance during the Holocene. A major limitation to this problem is represented by the extremely low dust concentration in Antarctic ice during interglacials. In this study, we analyzed the single‐grain mineralogy of more than 2, 300 mineral dust particles transported by winds to Dome C during four different time windows within the Holocene, the current interglacial. Comparing results with those obtained from dust deposited during the last glacial period, we observe that some minerals that are typically associated to glacial climate conditions in Patagonia almost disappear during Holocene, while the remaining minerals are compatible with a South American provenance in both climate periods. Data thus suggest that the dominant atmospheric circulation patterns did not experience a significant change with climate. However, data suggest an additional contribution from subtropical South American latitudes during Holocene. Key Points: The mineralogy of more than 2, 300 aeolian dust particles windblown to central East Antarctica (Dome C) during the Holocene was identified Disappearance of carbonate dust during the Holocene relates to sea level rise and suppressed deflation from the Argentinean shelf Aeolian dust suggests Pampean and Patagonian provenance in the Holocene and a lower latitude contribution, without major circulation changes